2006
DOI: 10.1179/joc.2006.18.5.554
|View full text |Cite
|
Sign up to set email alerts
|

Post-Neurosurgical Meningitis Due to Multidrug-ResistantAcinetobacter baumaniiTreated with Intrathecal Colistin: Case Report and Review of the Literature

Abstract: Intrathecal colistin (Polymxin E) is becoming an important option for the treatment of post-neurosurgical meningitis caused by multidrug resistant (MDR) Acinetobacter baumannii. We report a case of 28-year-old man who developed meningitis due to MDR A. baumannii associated with an external ventricular drain. The patient was cured using a 4-week course of intrathecal colistin 3.2 mg via external ventricular drain (EVD) daily without any serious side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
0
15
0
2
Order By: Relevance
“…Meningeal signs, focal neurological signs, and seizure are found in a minority of patients 60. Increased CSF white blood cell counts (ranging from 100 to several thousand cells per μL) are typical,19,21,23,27–32,35,37,44,53,58,60 with higher counts presumably found in those with delays in clinical suspicion of infection. However, cases of true infection that have no CSF white blood cells have been reported 60.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Meningeal signs, focal neurological signs, and seizure are found in a minority of patients 60. Increased CSF white blood cell counts (ranging from 100 to several thousand cells per μL) are typical,19,21,23,27–32,35,37,44,53,58,60 with higher counts presumably found in those with delays in clinical suspicion of infection. However, cases of true infection that have no CSF white blood cells have been reported 60.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Several cases of A. baumannii meningitis have been cured with i.v. colistin only (267,269,327,416), with reported levels in CSF of 1.25 mg/liter (CSF/serum ratio of 25%) (267,269); however, failures have also been reported that eventually responded only to intrathecal/ventricular administration (7,67,286,398,526). Dosing varies greatly between studies, but according to the Infectious Diseases Society of America, 5 mg of polymyxin B or 10 mg of colistin daily is recommended for adults (553).…”
Section: Existing Antimicrobial Agentsmentioning
confidence: 99%
“…baumannii is a successful nosocomial pathogen and is highly prevalent in Saudi intensive care units (ICUs), causing numerous outbreaks, many of them involving multidrug-resistant strains (Mah et al, 2001;Manzar, 2004;Al Shirawi et al, 2006;Bukhary et al, 2005;Yezli et al, 2014). There is evidence that resistance is increasing to many antibiotics in the Kingdom, including to carbapenems, which nevertheless remain the treatment of choice for most A. baumannii infections (Yezli et al, 2014).…”
Section: A Baumanniimentioning
confidence: 99%